2015
DOI: 10.5424/sjar/2015131-6750
|View full text |Cite
|
Sign up to set email alerts
|

Mating behaviour and gamete release in gilthead seabream (Sparus aurata, Linnaeus 1758) held in captivity

Abstract: The present study aimed to describe the reproductive behaviour of gilthead seabream (Sparus aurata) in captivity. Twenty-four mature gilthead seabream, divided in two tanks, were utilized for the present study. Reproductive behaviour was recorded using submersibles cameras. A total of 67 spawning events were analysed. The mean duration time that gilthead seabream spent spawning was 54 ± 4 min/day, during which mean number of individual spawning events was 5.6 ± 0.2. The mean volume of eggs produced by both bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…subordination) and may have evolved from similarly long‐term to permanent behavioural, morphological, physiological and environmental adaptations. In the case of S. aurata , Ibarra‐Zatarain and Duncan () observed a certain degree of dominance during the courtship and spawning rush. Therefore, when considering possible hierarchies developed by proactive S. aurata during spawning, reactive breeders were thought to implement these alternative reproductive tactics to increase their reproductive opportunities, to reduce their energetic cost and physical risk ( i.e ., injuries).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…subordination) and may have evolved from similarly long‐term to permanent behavioural, morphological, physiological and environmental adaptations. In the case of S. aurata , Ibarra‐Zatarain and Duncan () observed a certain degree of dominance during the courtship and spawning rush. Therefore, when considering possible hierarchies developed by proactive S. aurata during spawning, reactive breeders were thought to implement these alternative reproductive tactics to increase their reproductive opportunities, to reduce their energetic cost and physical risk ( i.e ., injuries).…”
Section: Discussionmentioning
confidence: 97%
“…(), juveniles of this species present defined proactive and reactive coping styles, but to date, no studies have been conducted on S. aurata breeders. Additionally, Ibarra‐Zatarain and Duncan () described the courtship and spawning behaviour of this species and reported that S. aurata showed a preference to spawn in pairs, which indicates how reproductive hierarchies that dominate contributions to progeny are established and maintained. In this sense, the present study aimed to consider whether and how S. aurata reproductive success is linked with stress‐coping styles.…”
Section: Introductionmentioning
confidence: 99%
“…It would appear that spawning in groups is uncommon in flatfish compared to round fish. Spawning in groups of one female with two or more males is common in round fish (Domeier & Colin, 1997) such as gilthead seabream (Sparus aurata) (Ibarra-Zatarain & Duncan, 2015). As was observed in the other eight flatfish species that spawned in pairs the Senegalese sole formed the pair on the bottom and swam up through the water column in synchrony.…”
Section: Discussionmentioning
confidence: 97%
“…The winter flounder was the exception and was described to release gametes in both a pair and a group (Breder, 1922;Stoner et al, 1999). The gamete release in a group consisted of a single female spawning with two or more males, which is a common spawning behaviour in round fish species (Domeier & Colin, 1997;Ibarra-Zatarain & Duncan, 2015). The eight species that spawned as a pair formed a pair on the bottom before making an upward synchronised coupled swim to release gametes.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the removal of embryonated eggs at a developmental stage prior to the minimum required stage could be understood as a bias that would result in the removal of all those families from parental matings that occurred only a few hours before collection. However, as the daily egg production in gilthead sea bream generally tends to be concentrated in a short space of time (Ibarra‐Zatarain & Duncan, ), the number of excluded embryonated eggs within each daily spawning analysed was not significant (<5%). Therefore, there is no evidence that the requirement of a minimum stage of development caused any bias in the spawning dynamics established for each daily spawning analysed.…”
Section: Discussionmentioning
confidence: 99%